Summer vegetables. - Time-Life Books (Alexandria, Va. : Time-Life Books, 1988)
"A Redefinition book"--Half t.p. Explains how to prepare the soil, plant and tend the garden, and harvest the crops you plant. Includes a dictionary of vegetables.
"A Redefinition book"--Half t.p.
Includes index.
Bibliography: p. 136.
Adult.
Adult
Keywords: Vegetable gardening; Vegetables; Vegetable gardening; Vegetables